Effectiveness of a self-management program for joint protection and physical activity in patients with rheumatoid arthritis: A randomized controlled trial. (April 2021) - Shao, Jung-Hua; Yu, Kuang-Hui; Chen, Su-Hui
Abstract: Background: Rheumatoid arthritis is a chronic, systemic disease, which results in progressive destruction of the joints and a reduction in quality of life. Joint protection can minimize injuries that worsen arthritis and pain and certain activities can help patients control or reduce the symptoms of this chronic disease. Objectives: To determine the effectiveness of a self-management program for joint protection and physical activity for patients with rheumatoid arthritis based on self-efficacy theory. Design: A two-arm (experimental vs control) randomized trial. Participants: Adult patients with rheumatoid arthritis were recruited from rheumatology departments of a medical center in Northern Taiwan. A total of 224 patients met the inclusion criteria and agreed to participate in the study. Methods: Eligible participants with rheumatoid arthritis were randomly assigned to either an 8-week program in self-management of joint protection and physical activity with nursing support (intervention group, n = 112) or standard care for rheumatology (control group, n = 112). Outcome variables were assessed at baseline and 2-, 3-, and 6-months after commencement of the intervention, which included measures of disease activity, and self-assessments for self-efficacy, quality of life, and self-management behaviors. Differences in outcome variables over time between the groups were analyzed with generalized estimating equations; the level of significance was set at p < 05. Results: The mean age of participants was 58.8 years, duration of the rheumatoid arthritis was 10 years, and most participants (86%) were female. Characteristics and assessment variables did not differ between the two groups at baseline. When compared with the control group at 6 months following initiation of the self-management program, participants in the intervention group demonstrated significantly greater improvement in physical functioning (B = 4.08, p < 05), self-efficacy of pain (B = 4.89, p < .05), and self-management behaviors (B = 4.65, p < 05). Conclusions: A self-management program based on self-efficacy theory that focused on joint protection and physical activities resulted in significant improvements in physical functioning, self-efficacy, and self-management behaviors 6 months following commencement of the intervention. Nurses provided individualized evaluations and support, which may have made it easier for participants to learn and perform the activities. After commencement of participation in the intervention, no improvements were seen until 6 months of participation. This delay may suggest patients with chronic disease may need a longer duration of self-management training and increased follow-up time to incorporate lifestyle changes. Future studies measuring long-term outcomes are suggested.